ABOUT THE POSSIBILITY OF PLASTICITY THEORY TO THE CALCULATION STRENGTH CONCRETE ELEMENTS FROM HIGH - , О. О., В. В., О. О. (Municipal economy of cities. Series: «Economy science», 2013)
The comparative analysis of the theoretical and experimental strength of the high-strength concrete specimens (concrete wedges, Gvozdev specimens, separate keys) and the results of the experimental investigation of the mentioned elements are expounded.